2018
DOI: 10.1097/acm.0000000000002233
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Lamppost: A Proposal for a Fourth Wave of Education for Collaboration

Abstract: Interprofessional education (IPE) is an increasingly popular educational model that aims to educate health care students to be better collaborators by enabling them to learn with, from, and about each other. IPE’s rising popularity is evident in the increase in scholarship on this topic over the last few decades. In this Perspective, the authors briefly describe three historical “waves” of IPE: managing the health workforce through shared curriculum, maximizing population health through health workforce planni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 36 publications
0
76
0
1
Order By: Relevance
“…Internationally there is also a strong move to team-based primary health care, often referred to as medical homes, to enhance integration of services and emphasize health promotion and chronic disease management (Hutchison et al , 2011; Naccarella et al , 2013). The evidence to date suggests that interprofessional collaboration contributes to the structures and processes of primary health care, including patient satisfaction and access to care (Donabedian, 2005; Hogg et al , 2008), however, limited knowledge exists about the impact that interprofessional collaborative teams have on patient health outcomes (Paradis and Whitehead, 2018). …”
Section: Introductionmentioning
confidence: 99%
“…Internationally there is also a strong move to team-based primary health care, often referred to as medical homes, to enhance integration of services and emphasize health promotion and chronic disease management (Hutchison et al , 2011; Naccarella et al , 2013). The evidence to date suggests that interprofessional collaboration contributes to the structures and processes of primary health care, including patient satisfaction and access to care (Donabedian, 2005; Hogg et al , 2008), however, limited knowledge exists about the impact that interprofessional collaborative teams have on patient health outcomes (Paradis and Whitehead, 2018). …”
Section: Introductionmentioning
confidence: 99%
“…Collaborative ideas and values have in recent years been incorporated within a wide variety of formal structures attached to the education, training and certification of clinicians (Paradis & Whitehead, 2018). Chief among these have been competency frameworks, such as the Royal College of Physicians and Surgeons of Canada (RCPSC) CanMEDS Physician Competency Framework (Frank, 2005;Frank et al, 2015), and the Accreditation Council for Graduate Medical Education (ACGME) Core Competencies, developed in the USA (see Holmboe, Edgar, & Hamstra, 2016).…”
Section: Institutionalizing the Collaborative Clinician: The Canmedsmentioning
confidence: 99%
“…This "collaborative ideal" acknowledges and pays tribute to the multiplicity of perspectives and contributions that constitute contemporary healthcare and endorses collaborative practice to improve the quality of care delivery. Indeed, collaboration has been proposed as a solution to a wide array of problems, from ineffective care to treatment errors, a fragmented system, patient and provider dissatisfaction and resource waste (Paradis & Whitehead, 2018). This is despite the fact that efforts to make care processes more collaborative have resulted in rather modest impacts on care quality and health outcomes (Reeves, Pelone, Harrison, Goldman, & Zwarenstein, 2017;Reeves, Perrier, Goldman, Freeth, & Zwarenstein, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 2015 review of 2191 IPE-related articles, Paradis and Whitehead found that only 6 articles discussed issues and solutions related to sociological power. 22 Paradis and Whitehead 23 have argued that the predominant theory informing IPE initiatives has been contact theory. 24,25 When applied to IPE, contact theory is premised on the notion that simply bringing different groups together will reduce prejudice and galvanize positive group relations.…”
Section: The Invisibility Of Power In Ipementioning
confidence: 99%